Long-term outcomes of high dose treatment and autologous stem cell transplantation in follicular and mantle cell lymphomas - a single centre experience - Boltežar, Lučka (Radiology and oncology (Ljubljana), 2017)
Background. Advanced follicular lymphoma (FL) and mantle cell lymphoma (MCL) are incurable diseases with conventional treatment. The high dose treatment (HDT) with autologous stem cell transplantation (ASCT), however, offers a certain proportion of these patients the prospect of a prolonged disease-free and overall survival. The aim of this study was to investigate the event free survival (EFS) and overall survival (OS) in patients with FL and MCL treated with ASCT. Patients and methods. Seventeen patients with FL and 29 patients with MCL were included, 15 of them were trans- planted to consolidate the response to second line treatment and 24 to consolidate their first remission, respectively. All were conditioned with total body irradiation (TBI) and high dose cyclophosphamide between 2006 and 2014 and all were transplanted with peripheral blood stem cells. Results. The estimated 5-year OS for FL was 87.8% (95% confidence interval CI 59.5%-96.8%) and for MCL 79.3% (95% CI 56.1%-91.1%), respectively. The estimated 5-year EFS for FL was 76.0% (95% CI 48.0%-90.3%) and for MCL 69.8% (95% CI 45.5%-84.8%), respectively. There were no secondary hematological malignancies observed in either group. Conclusions. Based on above results, the ASCT with TBI is a good treatment option in terms of long-term survival for patients with follicular and mantle cell lymphoma demonstrating a relatively low rate of late toxicities and secondary malignancies.
Keywords: autologous stem cell transplantation; avtologna presaditev matičnih celic; folikularni limfom; follicular lymphoma; limfom plaščnih celic; mantle cell lymphoma